1999
DOI: 10.1074/jbc.274.45.31882
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the Structural Basis for the Activation Properties of the Dopamine D1 Receptor Subtypes

Abstract: To delineate the structural determinants involved in the constitutive activation of the D1 receptor subtypes, we have constructed chimeras between the D1A and D1B receptors. These chimeras harbored a cognate domain corresponding to transmembrane regions 6 and 7 as well as the third extracellular loop (EL3) and cytoplasmic tail, a domain referred herein to as the terminal receptor locus (TRL). A chimeric D1A receptor harboring the D1B-TRL (chimera 1) displays an increased affinity for dopamine that is indisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
43
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 47 publications
13
43
0
Order By: Relevance
“…To narrow down the structural determinants within TRL involved in the subtype-specific ligand binding and G protein activation properties of the D1-like receptors, additional mutant receptors were constructed in which either the EL3 (10) or CT sequences (11) were swapped between the D1A and D1B receptors. Chimeric receptors harboring EL3 of their respective wild-type counterparts exhibited a complete reversal of agonist-mediated maximal activation of AC, whereas DA affinity and constitutive activity of the chimeras were only partially modulated by the exchange (10). In contrast, chimeric receptors harboring the CT of their respective wild-type counterparts displayed a full switch in DA affinity and constitutive activity, whereas DA potency decreased and agonist-mediated maximal activation of AC increased for both chimeras (11).…”
Section: Dopamine (Da)mentioning
confidence: 86%
See 3 more Smart Citations
“…To narrow down the structural determinants within TRL involved in the subtype-specific ligand binding and G protein activation properties of the D1-like receptors, additional mutant receptors were constructed in which either the EL3 (10) or CT sequences (11) were swapped between the D1A and D1B receptors. Chimeric receptors harboring EL3 of their respective wild-type counterparts exhibited a complete reversal of agonist-mediated maximal activation of AC, whereas DA affinity and constitutive activity of the chimeras were only partially modulated by the exchange (10). In contrast, chimeric receptors harboring the CT of their respective wild-type counterparts displayed a full switch in DA affinity and constitutive activity, whereas DA potency decreased and agonist-mediated maximal activation of AC increased for both chimeras (11).…”
Section: Dopamine (Da)mentioning
confidence: 86%
“…Previously, we have shown that a structural domain (referred to as the terminal receptor locus (TRL)) encompassing the sixth and seventh transmembrane regions (TM6 and TM7), third extracellular loop (EL3) and cytoplasmic tail (CT) plays an important role in the phenotypic expression of ligand binding and G protein coupling properties of D1-like receptors (10). To narrow down the structural determinants within TRL involved in the subtype-specific ligand binding and G protein activation properties of the D1-like receptors, additional mutant receptors were constructed in which either the EL3 (10) or CT sequences (11) were swapped between the D1A and D1B receptors.…”
Section: Dopamine (Da)mentioning
confidence: 99%
See 2 more Smart Citations
“…In a systematic binding study of the C-termini of all dopamine receptor subtypes, D5R but not D1R C-terminus selectively and strongly bound to a membrane-associated protein sorting nexin 1 (SNX1) [26] . In addition, the C-termini of D1-like receptors also governed their distinct binding affinity to agonists [27,28] . Swapping the C-termini of D1R and D5R resulted in the full switch of the affinities.…”
Section: Discussionmentioning
confidence: 99%